The Influence of Environmental Conditions and Entrepreneurial Orientation on Coffee Shop Performance Mediated by Innovation in Post Covid 19 Pandemic (Study on Business Coffee shop in Greater Malang, Indonesia) - Septiawan Vergian FACHROZIE; Rofiaty ROFIATY; Achmad Helmy JUMAHIR (International Journal of Environmental, Sustainability, and Social Science, 2022)
Environment and entrepreneurial orientation affect company performance. Innovation as a mediator of environmental condition and entrepreneurial approach on coffee shop performance. This quantitative research is explanatory. This study uses PLS for analysis. This finding company's performance after the Covid 19 epidemic based on environmental factors and entrepreneurial orientation. From November 2021 to April 2022, it was held at Malang Regency (Malang Districts, Malang City, and Batu City). This study includes the coffee business owner and investor making strategic decisions. This study analyzed 224 coffee shops in Malang that fulfilled the criteria. In other words the higher uncertainty on environmental condition (external factor) and entrepreneurial oriantation (internal factors) it trigger the high value of innovation in coffee shop. Innovation increased coffee shop performance. This means environmental conditions and entrepreneurial orientation influence innovation and coffee shop performance. Entrepreneurial orientation through innovation (mediator) affects coffee shop performance. The more environmental and entrepreneurial orientation affect innovation, the better the coffee shop's performance, especially post covid-19. Environmental factors and entrepreneurial orientation influence innovation, according to this study. Environmental conditions, entrepreneurial orientation, and innovation influence coffee shop performance both directly and indirectly. This study is one of the few example studies that exemine environmental condition, entrepreneurial orientation, innovation impact on company performance also the phenomena post covid 19 effect on coffee shop which is this phenomena include in this studies.